2018
DOI: 10.11114/jets.v6i5.3146
|View full text |Cite
|
Sign up to set email alerts
|

Being a Parent of a Child With Autism From Diagnosis to the University Years

Abstract: When literature is examined, it is seen that generally there are descriptive studies examining the effects of young children with autism in a certain age or age range on their parents' marital and family relationships as well as psychological conditions such as mourning, stress, anxiety, and depression. Longitudinal studies on the social experiences of parents of children with autism are scarce. It was observed that there was not a longitudinal study in Turkey, evaluating the emotional processes parents live t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
9
0
4
Order By: Relevance
“…There have also been couples or family counseling interventions that can be useful for parents and families living with and parenting individuals with autism. First, interventions that connect parents to parenting social support (Girli, 2018) and strengthen their partnerships given the normative stressors associated with parenting individuals with autism (Hartley, Barker, Baker, Seltzer, & Greenberg, 2012) are particularly useful. A second recommendation is drawn from Structural Family Therapy (Minuchin, 2012; Reiter, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been couples or family counseling interventions that can be useful for parents and families living with and parenting individuals with autism. First, interventions that connect parents to parenting social support (Girli, 2018) and strengthen their partnerships given the normative stressors associated with parenting individuals with autism (Hartley, Barker, Baker, Seltzer, & Greenberg, 2012) are particularly useful. A second recommendation is drawn from Structural Family Therapy (Minuchin, 2012; Reiter, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai reaksi orang tua terhadap kehadiran anak dengan ASD antara lain syok, bingung, marah, depresi dan pesimis tentang masa depan anak (Girli, 2018). Sebagian besar orang tua merasa kecewa, tidak bahagia, bahkan menolak kehadiran anak (Topan dkk., 2019).…”
Section: Pendahuluanunclassified
“…While the present study aims to evaluate sibling effects, the research pertaining to parents is relevant as parents and their interaction with all their children have a substantial impact on the outcomes of siblings. A signi cant portion of research regarding the familial experience of individuals with Autism Spectrum Disorder (ASD) has focused on the experience, supports and challenges faced by the parents of children with ASD (Hartley et al, 2010;Hsaio et al, 2016;Girli, 2018;Celia et al, 2020). For example, the concept of parents who become "Battle Weary" was explored by Celia et al (2020).…”
Section: Research On Parents Of Children With Asdmentioning
confidence: 99%
“…Parents who have to constantly advocate and "battle" for their children suffer signi cant stress and become weary over time. Girli (2018) explored the experiences of parents of children with ASD over their prime education years. They found that in addition to the consistent advocacy that parents have to make in order to ensure health and care for their child with ASD, as explored by Celia et al (2020), that they experience large shifts in mind-sets from their expectations from pre-birth to diagnosis.…”
Section: Research On Parents Of Children With Asdmentioning
confidence: 99%